2013
DOI: 10.3171/2012.10.jns12436
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the surgical Apgar score in a neurosurgical patient population

Abstract: The application of the surgical Apgar score to a neurosurgical cohort predicted 30-day postoperative mortality and complication rates as well as extended ICU and hospital stay. This readily calculated score may help neurosurgical teams efficiently direct postoperative care to those at highest risk of death and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…These findings are consistent with previous SAS validation studies in large patient populations, 9,10 other procedures, [11][12][13][14][15][16] and other surgical specialties. [17][18][19] The eSAS was a strong predictor of postoperative complications when treated as a dichotomized, categoric, or continuous variable. It is our opinion that the eSAS is more clinically useful when the score is used to stratify patients into high-risk (eSAS 6) and low-risk groups (eSAS >6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous SAS validation studies in large patient populations, 9,10 other procedures, [11][12][13][14][15][16] and other surgical specialties. [17][18][19] The eSAS was a strong predictor of postoperative complications when treated as a dichotomized, categoric, or continuous variable. It is our opinion that the eSAS is more clinically useful when the score is used to stratify patients into high-risk (eSAS 6) and low-risk groups (eSAS >6).…”
Section: Discussionmentioning
confidence: 99%
“…The SAS has now been externally validated in a number of large patient populations, 9,10 for specific procedures, [11][12][13][14][15][16] and for surgical specialties. [17][18][19] These studies have demonstrated significant predictive value of the SAS for postoperative morbidity and mortality.…”
Section: Perspectivementioning
confidence: 96%
“…Urrutia et al reported SAS allowed risk stratification and had good discriminatory power in 268 patients undergoing spinal surgery [20]. In a retrospective study of a general neurosurgical cohort, Ziewacz et al concluded the application of SAS predicted 30-day postoperative mortality and complication rates as well as extended intensive care unit and hospital stay [9]. Their results were convincing, but the study population included emergency, traumatic, spinal, and intracranial cases.…”
Section: Discussionmentioning
confidence: 99%
“…This scoring system has been validated more broadly for use in several cohorts of patients undergoing orthopedic, gynecologic, traumatic, urologic, or colorectal surgery [6, 7, 8]. In addition, Ziewacz et al showed that the use of SAS in a general neurosurgical population can allow risk stratification [9]. However, the diversity of the neurosurgical field, from emergency to elective or brain to spinal surgery, should be taken into consideration, and the efficacy of SAS in the setting of each procedure should be accessed.…”
Section: Introductionmentioning
confidence: 99%
“…3 After neurosurgical procedures Ziewacz et al demonstrated a significant association not only between SAS and complication rates, but also between SAS and hospital and ICU length of stay, with lower scores predictive of higher complication rates and longer hospital and ICU stays. 6 In gynecologic oncology Zighelboim et al reported that a SAS of 4 or less resulted in a 7.4-fold increased odds of a major complication (95% CI 2.9e18.8, p <0.0001) in patients with stage III/IV ovarian cancer undergoing cytoreductive surgery. 5 To date only 2 published studies have examined the use of SAS in urological patient cohorts.…”
Section: Discussionmentioning
confidence: 97%